Is an ECU parallel currency the way to achieve European monetary integration? - Peter Bofinger (Intereconomics, 1985)
A very lively debate has now developed about the future of European monetary policy. Dr. Peter Bofinger analyses the arguments for and against the promotion of the ECU as a parallel currency.
Keywords: 330; European Monetary System